2014
DOI: 10.1016/j.cub.2014.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Color Constancy for an Unseen Surface

Abstract: The illumination of a scene strongly affects our perception of objects in that scene, e.g., the pages of a book illuminated by candlelight will appear quite yellow relative to other types of artificial illuminants. Yet at the same time, the reader still judges the pages as white, their surface color unaffected by the interplay of paper and illuminant. It has been shown empirically that we can indeed report two quite different interpretations of "color": one is dependent on the constant surface spectral reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 28 publications
1
34
1
Order By: Relevance
“…However, such a claim would need to confront recent evidence that color can be perceptually represented outside of consciousness, even when the latter is measured objectively. In particular, using a metacontrast masking paradigm, Norman et al (2014) found priming effects implicating surface color representations (implying constancy based perception) despite d` not differing significantly from zero. In Phillips (forthcoming-a), I discuss whether such cases of perceptual representation amount to perception of the same fundamental kind as ordinary conscious perception by the individual.…”
Section: Back To Naïve Introspectionmentioning
confidence: 92%
“…However, such a claim would need to confront recent evidence that color can be perceptually represented outside of consciousness, even when the latter is measured objectively. In particular, using a metacontrast masking paradigm, Norman et al (2014) found priming effects implicating surface color representations (implying constancy based perception) despite d` not differing significantly from zero. In Phillips (forthcoming-a), I discuss whether such cases of perceptual representation amount to perception of the same fundamental kind as ordinary conscious perception by the individual.…”
Section: Back To Naïve Introspectionmentioning
confidence: 92%
“…For example, subjects fail to detect subliminal primes even in controlled settings, but such stimuli can still drive behavioral responses (see e.g. Norman et al 2014;Faivre et al 2014; see also Ansorge et al 2014 for a review). On the other hand, several studies have shown that percepts which were not consciously registered by the subjects can later be brought into consciousness by attentional cues directed at the location of the stimulus after its disappearance (Kentridge 2013;Sergent et al 2013;Thibault et al 2016).…”
Section: The Problem Of Unconscious Perceptionmentioning
confidence: 99%
“…The central question we address here is whether the same is true of shape constancy. This question is of some importance because the extant data suggest that shape constancy appears to operate in ways that are different from those that Norman et al (2014) found for color constancy.…”
Section: Introductionmentioning
confidence: 94%
“…The present series of experiments arose through consideration of a recent paper by Norman, Akins, Heywood, and Kentridge (2014). In a series of metacontrast masking experiments, they found that color constancy can be achieved unconsciously and with extraordinary speed.…”
Section: Introductionmentioning
confidence: 99%